Rapid and sensitive LC method for the analysis of Gemifloxacin in Human plasma - Chakrabarty, Uday Sankar; Das, Ayan; Bhaumik, Uttam; Chatterjee, Bappaditya; Nandi, Utpal; Pal, Tapan Kumar (Vieweg Verlag, 2009)
A simple liquid chromatographic method for the determination of gemifloxacin (CAS number 175463-14-6) in human plasma has been developed. An aliquot quantity of 1 mL plasma sample was taken and 0.1 mL internal standard was added and mixed. 1 mL methanol was added to it. The mixture was then sonicated for 10 min followed by 20 min centrifugation at 5000 rpm (g = 3600). The supernatant layer was separated and filtered through simple filtration unit (membrane filter, 0.45 μm) and injected into the LC system consisting of Hypersil BDS, C18 (250 × 4.6 mm, 5 μm particle size) column, using 1% formic acid : methanol = 65:35 (v/v) as mobile phase with ultra violet detection at 328 nm. Lower limit of detection was 20 ng mL−1 and lower limit of quantitation was 50 ng mL−1. Maximum between-run precision was 14.614%. Mean extraction recovery was found to be 87.32 to 89.32%. Stability study showed that after three freeze-thaw cycles the loss of three quality control samples were less than 10%. Samples were stable at room temperature for 12 h and at −20 °C for 3 months. Before injecting into LC system, the processed samples were stable for at least 8 h. The method was used to perform bioequivalence study in human volunteers.